1,2-Dibenzoyl Cyclopentadiene Derivative as New Potential Chelating Agent in Geological Materials - H. ARBAB ZAVAR, MOHAMMAD; FARAMARZ TAYYARI, SAYYED; EVAZMOGHADAM, SIMA; CHAMSAZ, MAHMMUD (Asian Journal of Chemistry, 2010)
In this paper, 2,3-bis(p-metboxybenzoyl)cyclopentadiene (DPMBCP) has been studied as a chelating agent and pKa value was determined by means of spectrophotometric measurements. The sigmoid curve of optical density against pH was constructed and pKa value was obtained from log I against pH, having the value of 8.27 ± 0.02 at λ = 421 nm and temperature (t) = 25 ± 0.1°C. Interaction of Fe3+, Ce4+, La3+ with DPMBCP in water/ethanol (1:1) (v/v) solution studied and for Fe3+ and Ce4+ leads to the formation of complex species in the recommended condition. The optimum conditions for solvent, the pH and concentration of ligand were studied and interference effects, linear range detection limit, specific absorptivity, Sandell sensitivity and other analytical parameters were also evaluated. The method is sensitive, simple and an alternative for spectrophotometric determination of Fe3+ and Ce4+, but not for La3+. The reproducibility for Fe3+ is shown by a relative deviation of about 0.67%. This system obeys the Beer's law and is suitable for iron determination in the concentration range from 0.1 to 1 μg/cm3, with a correlation coefficient (r2) of 0.9992. Analytical application has been tested for geological materials (iron-rock), in which the results were compared with atomic absorption measurement Very good concordances were obtained between these two different techniques, suggesting the potential of present spectrophotometric method for iron analysis.